Coxiella burnetii type IVB secretion system Region I genes are expressed early during infection of host cells - Morgan, John K. (2010)
Analysis of the Coxiella burnetii RSA 493 (Nine Mile Phase I strain) genome revealed open reading frames with significant homology to the type IVB secretion system (T4BSS) of Legionella pneumophila. The T4BSS genes exist primarily at two loci, designated regions I (RI) and II. In C. burnetii, little is known about the T4BSS regions and the role they play in establishing and/or maintaining infection. C. burnetii T4BSS RI contains genes arranged in three linkage groups: (i) icmW→CBU1651→icmX, (ii) icmV→dotA→CBU1647, (iii) icmT→icmS→dotD→dotC→dotB→CBU1646. We used RT-PCR to demonstrate transcriptional linkage within the groups, and that icmX, icmV, and icmT are transcribed de novo by 8 hours post infection (hpi). We then examined transcript levels for icmX, icmW, icmV, dotA, dotB and icmT during the first 24 hours of an infection using RT-qPCR. Expression initially increased for each gene, followed by a decrease at 24 hpi. Subsequently, we analyzed IcmT protein levels during infection and determined that expression increases significantly from 8 to 24 hpi then remains relatively constant. These data demonstrate temporal changes in the RNA of several C. burnetii T4SS RI homologs and the IcmT protein. These changes correspond to early stages of the C. burnetii infectious cycle.